The Relevance of Gender for Excellent Research and Innovation: An Opinion - Yvonne Galligan (Irish Journal of Academic Practice, 2023)
This piece argues that the integration of sex and/or gender in research improves the quality of the research, contributes to excellence in the research process and makes the outcomes beneficial to society.